Rising rate of cesarean section - a year review - Subedi, Shanti (Journal of Nobel Medical College, 2012)
Caesarean section is one of the most common surgeries performed in modern obstetrics. The rising trend of caesarean section in modern obstetrics is a major concern in health care system all over the world. With all the limited health care resources in a developing country like Nepal, this rising trend definitely has major implication. Rates of caesarean section countries in many countries have increased beyond the recommended level (WHO, 1985). Current available data from developed countries revealed morbidity and mortality from CS is more than in vaginal delivery for both the mother and fetus. Thus this study was conducted to evaluate the rate and indication for CS and to identify the measures to decrease its incidence if possible. Our results shows the foetal distress as the most common indication for Cesarean section in a eastern part of Nepal, which can be minimized significantly if a proper and timely investigation is carried out. DOI: http://dx.doi.org/10.3126/jonmc.v1i2.7303 Journal of Nobel Medical College (2012), Vol.1 No.2 p.72-76